Answer:
Therefore
and
are fundamental solution of the given differential equation.
Therefore
and
are linearly independent, since ![W(e^{-4x},e^{5x})=9e^x\neq 0](https://tex.z-dn.net/?f=W%28e%5E%7B-4x%7D%2Ce%5E%7B5x%7D%29%3D9e%5Ex%5Cneq%200)
The general solution of the differential equation is
![y=c_1e^{-4x}+c_2e^{5x}](https://tex.z-dn.net/?f=y%3Dc_1e%5E%7B-4x%7D%2Bc_2e%5E%7B5x%7D)
Step-by-step explanation:
Given differential equation is
y''-y'-20y =0
Here P(x)= -1, Q(x)= -20 and R(x)=0
Let trial solution be ![y=e^{mx}](https://tex.z-dn.net/?f=y%3De%5E%7Bmx%7D)
Then,
and ![y''=m^2e^{mx}](https://tex.z-dn.net/?f=y%27%27%3Dm%5E2e%5E%7Bmx%7D)
![\therefore m^2e^{mx}-m e^{mx}-20e^{mx}=0](https://tex.z-dn.net/?f=%5Ctherefore%20m%5E2e%5E%7Bmx%7D-m%20e%5E%7Bmx%7D-20e%5E%7Bmx%7D%3D0)
![\Rightarrow m^2-m-20=0](https://tex.z-dn.net/?f=%5CRightarrow%20m%5E2-m-20%3D0)
![\Rightarrow m^2-5m+4m-20=0](https://tex.z-dn.net/?f=%5CRightarrow%20m%5E2-5m%2B4m-20%3D0)
![\Rightarrow m(m-5)+4(m-5)=0](https://tex.z-dn.net/?f=%5CRightarrow%20m%28m-5%29%2B4%28m-5%29%3D0)
![\Rightarrow (m-5)(m+4)=0](https://tex.z-dn.net/?f=%5CRightarrow%20%28m-5%29%28m%2B4%29%3D0)
![\Rightarrow m=-4,5](https://tex.z-dn.net/?f=%5CRightarrow%20m%3D-4%2C5)
Therefore the complementary function is = ![c_1e^{-4x}+c_2e^{5x}](https://tex.z-dn.net/?f=c_1e%5E%7B-4x%7D%2Bc_2e%5E%7B5x%7D)
Therefore
and
are fundamental solution of the given differential equation.
If
and
are the fundamental solution of differential equation, then
![W(y_1,y_2)=\left|\begin{array}{cc}y_1&y_2\\y'_1&y'_2\end{array}\right|\neq 0](https://tex.z-dn.net/?f=W%28y_1%2Cy_2%29%3D%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7Dy_1%26y_2%5C%5Cy%27_1%26y%27_2%5Cend%7Barray%7D%5Cright%7C%5Cneq%200)
Then
and
are linearly independent.
![W(e^{-4x},e^{5x})=\left|\begin{array}{cc}e^{-4x}&e^{5x}\\-4e^{-4x}&5e^{5x}\end{array}\right|](https://tex.z-dn.net/?f=W%28e%5E%7B-4x%7D%2Ce%5E%7B5x%7D%29%3D%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7De%5E%7B-4x%7D%26e%5E%7B5x%7D%5C%5C-4e%5E%7B-4x%7D%265e%5E%7B5x%7D%5Cend%7Barray%7D%5Cright%7C)
![=e^{-4x}.5e^{5x}-e^{5x}.(-4e^{-4x})](https://tex.z-dn.net/?f=%3De%5E%7B-4x%7D.5e%5E%7B5x%7D-e%5E%7B5x%7D.%28-4e%5E%7B-4x%7D%29)
![=5e^x+4e^x](https://tex.z-dn.net/?f=%3D5e%5Ex%2B4e%5Ex)
![=9e^x\neq 0](https://tex.z-dn.net/?f=%3D9e%5Ex%5Cneq%200)
Therefore
and
are linearly independent, since ![W(e^{-4x},e^{5x})=9e^x\neq 0](https://tex.z-dn.net/?f=W%28e%5E%7B-4x%7D%2Ce%5E%7B5x%7D%29%3D9e%5Ex%5Cneq%200)
Let the the particular solution of the differential equation is
![y_p=v_1e^{-4x}+v_2e^{5x}](https://tex.z-dn.net/?f=y_p%3Dv_1e%5E%7B-4x%7D%2Bv_2e%5E%7B5x%7D)
and
![\therefore v_2=\int \frac{y_1R(x)}{W(y_1,y_2)} dx](https://tex.z-dn.net/?f=%5Ctherefore%20v_2%3D%5Cint%20%5Cfrac%7By_1R%28x%29%7D%7BW%28y_1%2Cy_2%29%7D%20dx)
Here
,
,
,and ![R(x)=0](https://tex.z-dn.net/?f=R%28x%29%3D0)
![\therefore v_1=\int \frac{-e^{5x}.0}{9e^x}dx](https://tex.z-dn.net/?f=%5Ctherefore%20v_1%3D%5Cint%20%5Cfrac%7B-e%5E%7B5x%7D.0%7D%7B9e%5Ex%7Ddx)
=0
and
![\therefore v_2=\int \frac{e^{5x}.0}{9e^x}dx](https://tex.z-dn.net/?f=%5Ctherefore%20v_2%3D%5Cint%20%5Cfrac%7Be%5E%7B5x%7D.0%7D%7B9e%5Ex%7Ddx)
=0
The the P.I = 0
The general solution of the differential equation is
![y=c_1e^{-4x}+c_2e^{5x}](https://tex.z-dn.net/?f=y%3Dc_1e%5E%7B-4x%7D%2Bc_2e%5E%7B5x%7D)